Effectiveness of Forestry Law Enforcement Against Forest Destruction in Central Lombok: Efektivitas Penegakan Hukum Kehutanan terhadap Perusakan Hutan di Lombok Tengah - Hera Alvina S; Muhammad Rifaldi Setiawan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Forests play an important role in maintaining ecological balance, supporting community livelihoods, and protecting biodiversity. However, forest destruction in Central Lombok remains a serious problem due to illegal logging, forest encroachment, land conversion, and limited law enforcement capacity. This study aims to analyze the effectiveness of forestry law enforcement against forest destruction in Central Lombok. The discussion is based on statutory regulations, literature review, and interview findings related to forestry law enforcement practices. The results show that forestry law enforcement in Central Lombok has not been fully effective. Although Indonesia already has legal instruments such as Law Number 41 of 1999 concerning Forestry and Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction, implementation in the field still faces various obstacles. These obstacles include limited personnel, inadequate monitoring facilities, weak inter-agency coordination, low legal awareness, and high community dependence on forest resources. In addition, sanctions have not always created a strong deterrent effect. Therefore, strengthening institutional coordination, improving supervision, increasing community legal awareness, and providing sustainable economic alternatives are needed to protect forest areas more effectively.